Phylogeny of Geoglossomycetes with species diversity in China - Hongli Su; Kevin D. Hyde; Qing Cai; Wenyan Chen; Fatimah Al-Otibi; K.W. Thilini Chethana; Zhu L. Yang; Qi Zhao (Mycology)
Geoglossomycetes is a class within the phylum Ascomycota that accommodates a single order and a single family, comprising nine genera. Geoglossomycetes is traditionally referred to as “earth tongues”. The class is characterised by tongue-shaped to clavate, stipitate, black ascomata covered with or without black setae, a swollen ascigerous portion, a cylindric stipe, filiform, septate paraphyses, cylindrical-clavate, 4–8-spored asci, and filiform or falciform, multi-septate, dark brown to hyaline ascospores. In this study, we examined 34 samples from four genera in China. Based on ecological comparisons, morphological studies, and phylogenetic analyses inferred from the combined internal transcribed spacer (ITS) regions and the large subunit of the ribosomal RNA gene (LSU), we introduce ten new species of Geoglossomycetes, and identify four known species. In addition, we summarise the sexual morph characters of all species within the two largest genera, Geoglossum and Trichoglossum.